IMF Survey, Volume 36 Issue 02. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2007)
Montenegro, IMF membership, Peru loan, Lebanon, Murilo Portugal interview, IMF technical assistance (TA), Vietnam and WTO, Colombia, foreign direct investment, gender and economics, Arab economies, France and 35-hour week.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet